Religious Democratic Leadership Style of School Principals in Improving Education Quality at Madrasah Aliyah MBS Klaten - Yusriani Ni'am; Istanto Istanto (Journal of Educational Sciences, 2026)
This study aims to describe the characteristics of religious democratic leadership, its implementation, and its impact on the quality of education at Muhammadiyah Islamic Senior High School MBS Klaten. This study employed a qualitative method, with data collection techniques including interviews, observations, and documentation involving the principal, teachers, and institutional staff. The data were then analyzed through data reduction, data presentation, and conclusion drawing and verification. The results showed that the madrasah principal applied a religious democratic leadership style, which was reflected in openness in deliberation, the involvement of teachers in decision-making, and spiritual exemplary behavior in the form of habitual worship, moral guidance, and the strengthening of religious culture in the madrasah environment. The application of this leadership style has a direct impact on improving teacher professionalism, learning effectiveness, student character development, and the overall quality of the institution. Thus, religious democratic leadership has been proven to contribute significantly to improving the quality of education at MA MBS Klaten.